2016
DOI: 10.1242/jcs.180141
|View full text |Cite
|
Sign up to set email alerts
|

PI3K regulates endocytosis after insulin secretion by mediating signaling crosstalk between Arf6 and Rab27a

Abstract: In secretory cells, endocytosis is coupled to exocytosis to enable proper secretion. Although endocytosis is crucial to maintain cellular homeostasis before and after secretion, knowledge about secretagogue-induced endocytosis in secretory cells is still limited. Here, we searched for proteins that interacted with the Rab27a GTPase-activating protein (GAP) EPI64 (also known as TBC1D10A) and identified the Arf6 guanine-nucleotide-exchange factor (GEF) ARNO (also known as CYTH2) in pancreatic β-cells. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
3
21
0
Order By: Relevance
“…Furthermore, in the presence of glucose, ARNO binds the GAP for Rab27a, the latter being involved in exocytosis. This intricate crosstalk between phosphatidylinositol phosphate (PIP), ARFs and Rabs responds at least partially to cellular demands of endocytosis and exocytosis [ 112 ].…”
Section: The Endomembrane System Is Formed By Compartments Of Uniqmentioning
confidence: 99%
“…Furthermore, in the presence of glucose, ARNO binds the GAP for Rab27a, the latter being involved in exocytosis. This intricate crosstalk between phosphatidylinositol phosphate (PIP), ARFs and Rabs responds at least partially to cellular demands of endocytosis and exocytosis [ 112 ].…”
Section: The Endomembrane System Is Formed By Compartments Of Uniqmentioning
confidence: 99%
“…The IP pathway (Fig 1) plays important roles in regulating essential biological processes from yeast to humans, including mRNA transport from the nucleus to the cytoplasm (Wickramasinghe, et al, 2013), transcriptional regulation (Millard, et al, 2013; Steger, et al, 2003), embryogenesis (Seeds, et al, 2015), endocytosis (Yamaoka, et al, 2015), and ciliary function and signal transduction (Chavez, et al, 2015). We recently showed that this pathway controls transcription and allelic exclusion of variant surface glycoprotein (VSG) genes in T. brucei (Cestari and Stuart, 2015), allowing T. brucei to evade the host immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Rab27s regulate endocytosis in exocytic pancreatic cell lines via its interaction with coronin 3(Kimura et al, 2008; Yamaoka et al, 2016), an actin-bundling protein that supports invagination for clathrin-dependent and clathrin-independent endocytosis(Mooren et al, 2012). Our data suggests that Rab27 isoforms regulates the endocytosis of larger molecular weight αsyn species in neurons.…”
Section: Discussionmentioning
confidence: 99%